Peningkatan Hasil Belajar Melalui Media Visual pada Mata Pelajaran IPA Siswa Kelas V Sekolah Dasar - Sulastri, Arum (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This research was conducted because of the low learning outcomes of fifth grade students at SDN11 Tulang Bawang Tengah in science subjects, the methods and learning media used by the teacher were less varied, and students were less active in learning. The purpose of this study was to improve the learning outcomes of fifth graders at SD 11 Tulang Bawang Tengah in science subjects with the subject of the process of soil formation using visual media. This research is a classroom action research. The subjects in this study were the fifth grade students of SD 11 Tulang Bawang Tengah with a total of 28 students. This research took place in two cycles. Cycle I and cycle II consist of 2 meetings. Data collection techniques in this study were observation and objective tests. The instruments used are observation sheets and objective test questions. The data analysis technique used is descriptive quantitative and descriptive qualitative. The success indicator is determined if the class average increases from pre-action, cycle I and cycle II. The results showed that students' science learning outcomes had increased. This is indicated by the increase in the average value of the class at the time of pre-action 65.71 increased to 69.64 in the first cycle and then increased again in the second cycle to 79.19.